Cultural Expression of Aesthetic in Laker Paintings of Sanggar Ganesha in Palembang - Mubarat, Husni; Suharto, Suharto; Pebriyani, Nyoman Dewi (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2024)
Social, economic, and demographic changes in Palembang, such as artists' migration to Yogyakarta and shifting community preferences towards Laker paintings, have impacted the sustainability of the aesthetic of Laker paintings at Sanggar Ganesha in Palembang. This research aims to examine the aesthetic elements of Laker paintings and how these elements reflect local wisdom and reveal symbolic meanings embedded in Laker paintings at Sanggar Ganesha, Palembang. The research method employed is qualitative descriptive. Data collection involved direct observation of Laker paintings, in-depth interviews with artists and key informants at Sanggar Ganesha, and literature review from relevant sources. Data analysis utilized intra-aesthetic analysis techniques to examine visual elements and painting techniques, and extra-aesthetic analysis to explore social, cultural, and philosophical aspects within Palembang's Laker paintings. Findings reveal that Laker paintings at Sanggar Ganesha, Palembang, exhibit unique aesthetic richness reflected through the use of traditional mediums such as Lak varnish, gold leaf, and Chinese ink. These mediums not only provide distinctive visual dimensions but also preserve the authenticity of Laker painting techniques. Elements like monochromatic golden hues, black color usage to highlight crucial details, and the smooth texture derived from Lak varnish application enrich both visual and symbolic dimensions of the paintings. Additionally, Laker paintings at Sanggar Ganesha depict cultural symbols and traditional Palembang values such as the Masjid Agunge, Ampera Jembatan, Rumah Rakit, and the atmosphere of the Sungai Musi, all reflected in visual representations.